Rekayasa Proses Bisnis Layanan Pengiriman Paket - Tiur Gantini; Yasinta Kurnia Wijaya (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
During the pandemic, companies engaged in package delivery did not experience a negative impact, instead they experienced rapid development and new companies emerged. This study discusses business process engineering related to package delivery services in courier companies. Data research was collected through an interview method with one of the staff working in Jalur Nugraha Ekakurir (JNE) company Setrasari Bandung and a direct observation method related to this service. From the data research, it is known that the business processes ‘AS-IS’ are then carried out in business process engineering. It is recommended that agents and branches be able to sort packages so that if the package is in the nearest area it can be sent directly to the intended address according to the type of package chosen by the customer, with costs that include insurance for damage and loss of goods. And the courier on duty has been confirmed to be well trained, passed the test and knows the conditions of the location in the area very well.